The Influence of Digital Literacy, Marketing Strategy, and Business Duration on The Income of MSMES Using E-Catalogs in Denpasar City - Suwandewi, Putu Ayu Meidha; Adiyadnya, Made Santana Putra (Jurnal Indonesia Sosial Sains, 2025)
The development of the current era where digitalization is growing rapidly indirectly shifts the pattern of business people in running a business. Utilizing the marketplace as a medium to interact with buyers is an opportunity to be able to develop a business with a wider reach. The government, which is also active in the procurement process of goods and services, also uses electronic media in the procurement of goods and services to create a transparent shopping climate, fair competition, and shopping at reasonable prices. The purpose of this study is to determine the influence of digital literacy, marketing strategies, and business duration in increasing the income of MSMEs using E-Catalog in Denpasar City. This research is a type of quantitative research. Data collection techniques through observation and interviews conducted by researchers to MSME actors using E-Catalog in Denpasar City. The results of this study show that digital literacy, marketing strategies, and business length have a positive and significant effect on the income of MSMEs using E-Catalog in Denpasar City.